The effect of corporate social responsibility, capital structure, and current ratio on profitability with firm size as moderating variables on companies in the Jakarta Islamic Index (JII) 2016-2020 - Fitriyani, Arum Teguh; Annisa, Arna Asna (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
Profitability is a measurement of a company’s financial performance in generating profits. This study aims to determine the factors that affect profitability by analyzing the relationship between corporate social responsibility, capital structure, and current ratio on company profitability moderated by company size. This research is quantitative, with a population of 30 companies listed on the Jakarta Islamic Index (JII). The sampling technique used was the purposing sampling technique, as many as 12 companies registered at JII for the 2016-2020 period. The data analysis technique in this study used descriptive statistical data analysis. This research shows that corporate social responsibility significantly influences profitability, and capital structure negatively impacts profitability. The current ratio does not have a significant influence on profitability. Firm size does not significantly influence profitability, and the firm size can moderate corporate social responsibility, capital structure, and a current ratio of profitability. This research contributes to Islamic accounting and provides information about factors